The Impact of ESG Practices on Sustainable Companies Performance in Indonesia - Darsono, Susilo Nur Aji Cokro; Ma'la, Ainun (UMSurabaya Publishing, 2024)
ESG practices aim to minimize a company's risks by caring about environmental, social, and governance aspects. Implementing ESG practices certainly has benefits for companies, namely improving the company's reputation. This research aims to measure the ESG practices of Indonesian companies listed on the Indonesian Stock Exchange. The research analysis uses the panel regression method. Previous researchers faced limitations in studying companies implementing ESG, leading to a limited number of analyzed companies. Therefore, using data obtained from Tobin's Q can distinguish this study. Based on the data processing results, environmental and ROA variables significantly positively impact the company's performance or reputation. However, social and governance variables do not influence the company's reputation, possibly due to various factors causing companies to focus less on the performance of these two variables